Punishment in The Nickel Boys novel by Colson Whitehead - Agus Mulyadi (Morphosis: Journal of Literature, 2024)
The study aimed to analyze the issue of punishment depicted through the main character and to reveal the impact of punishment on the main character in The Nickel Boys (2019) novel by Colson Whitehead. Punishment is an action given to a person or convicted for the violation that occurred. The form of punishment given to someone can be in the form of flogging, forced labor, and imprisonment. Michel Foucault’s postmodernism (1977) described, torture is a form of punishment that is carried out directly on the body that causes pain to the recipient’s body. Meanwhile punishment with confinement is carried out by controlling the body, time, activity, and soul so that the violation did not happen again in the future. Thus there was torture and punishment to make humans disciplined. The research method in this study used qualitative method to analyze the occurrence of punishment through the main character in the novel. The results of this study indicated that the practice of punishment that occurred in The Nickel Boys is an act that unfair to the main character. Besides it, punishment also affected the main character’s mental condition, which resulted in loss-motivation, anxiety, rebellion and escape. Keywords: discipline, punishment, punish, torture.